Notch3 is dispensable for thymocyte β-selection and Notch1-induced T cell leukemogenesis. - Sara Suliman; Joanne Tan; Keli Xu; Philaretos C Kousis; Paul E Kowalski; Greg Chang; Sean E Egan; Cynthia Guidos (PLoS ONE, 2011)
Notch1 (N1) signaling induced by intrathymic Delta-like (DL) ligands is required for T cell lineage commitment as well as self-renewal during "β-selection" of TCRβ⁺CD4⁻CD8⁻ double negative 3 (DN3) T cell progenitors. However, over-expression of the N1 intracellular domain (ICN1) renders N1 activation ligand-independent and drives leukemic transformation during β-selection. DN3 progenitors also express Notch3 (N3) mRNA, and over-expression of ligand-independent mutant N3 (ICN3) influences β-selection and drives T cell leukemogenesis. However, the importance of ligand-activated N3 in promoting β-selection and ICN1-induced T cell leukemogenesis has not been examined. To address these questions we generated mice lacking functional N3. We confirmed that DN3 progenitors express N3 protein using a N3-specific antibody. Surprisingly however, N3-deficient DN3 thymocytes were not defective in generating DP thymocytes under steady state conditions or in more stringent competition assays. To determine if N3 co-operates with N1 to regulate β-selection, we generated N1;N3 compound mutants. However, N3 deficiency did not exacerbate the competitive defect of N1⁺/⁻ DN3 progenitors, demonstrating that N3 does not compensate for limiting N1 during T cell development. Finally, N3 deficiency did not attenuate T cell leukemogenesis induced by conditional expression of ICN1 in DN3 thymocytes. Importantly, we showed that in contrast to N1, N3 has a low binding affinity for DL4, the most abundant intrathymic DL ligand. Thus, despite the profound effects of ectopic ligand-independent N3 activation on T cell development and leukemogenesis, physiologically activated N3 is dispensable for both processes, likely because N3 interacts poorly with intrathymic DL4.